Consumer motivations for participation in the sharing economy: A goal-framing perspective - João Miguel O. Cotrim; Francisco G. Nunes (Sustainable Futures)
The SE (SE) is reshaping industries and consumer behaviours, yet existing research lacks a unified theoretical explanation of the psychological drivers behind participation in Sharing-Based Programs (SBPs). To address this gap, this study explores why consumers choose to engage with SBPs, focusing on hedonic, gain, and normative motives using goal-framing theory as a lens and integrating the sharing–exchange continuum. The purpose of this research is to empirically test how these motives influence participation and how these patterns vary across different platform types. Based on a between-subject experimental design with 320 participants, results reveal that consumers perceive SBPs as aligned with collective societal norms, thus activating normative goals that foster collaboration, fairness, and pro-social behaviour. This alignment significantly supports social and environmental sustainability outcomes. By extending goal-framing theory into the SE context, this study contributes theoretically and offers actionable insights for businesses to design inclusive, purpose-driven, and sustainability-oriented platforms that resonate with users’ underlying motivations.